The meanings of visual art education on emotional, cognitive and social developments of pupils - Abdolmalekian, Sahar (2019)
The aim of this study was to study meanings of visual art education on emotional, cognitive and social development of pupils. The goal was also to discover the different dimensions of these developmental factors in relation with art education. For describing these meanings, the method of open–ended interview was done, through which data from 5 number of teacher training students and 2 art teachers was gathered. Data was analysed by conventional content analysis method in section of results, and for assessing the accountability of findings, they have been compared with the reference data of section two, in the final section of discussion. According to the main findings of this study, the added value of visual art education is that it can improve pupils’ emotional, cognitive and social development, while there are divers number of themes in meanings of pupils’ learning, related to each developmental aspect. This study aims to create ideas for future studies of visual art education regarding the neoliberal policies dominant in educational settings, particularly in developing countries, considering the political and social problems there.